Television viewing habits and their influence on physical activity and childhood overweight - Gisele F. Dutra; Cristina C. Kaufmann; Alessandra D.B. Pretto; Elaine P. Albernaz (Elsevier, 2015)
OBJECTIVES: To assess the prevalence of television (TV) viewing habits and their association with childhood sedentary lifestyle and overweight in 8-year-old children, from a cohort in a city in Southern Brazil.METHODS: A prospective cohort study with hospital screening of all births that occurred from September of 2002 to May of 2003. This study refers to a cross-sectional analysis of data collected during the cohort's follow-up conducted at 8 years of age. To evaluate the level of physical activity, a physical activity questionnaire for children and adolescents was used (PAQ-C), during the consultation at 8 years of age.RESULTS: Of the 616 interviewed children, a prevalence of sedentary lifestyle > 70% was found, as well as the habit of watching TV for more than two hours a day in 60% of the sample, regardless of gender (p = 0.30), income (p = 0.57), or family socioeconomic level (p = 0.90). The daily time spent watching TV was inversely associated with physical activity (p < 0.05) and positively associated with excess weight (p < 0.01). Regarding physical activity, running was the most frequently practiced sports modality among the population.CONCLUSIONS: Considering the high prevalence of sedentary lifestyle and children who watch TV for an excessive period of time, it is necessary to motivate such individuals to perform interactive activities, as well as promote a more active lifestyle, by decreasing the time children spend in front of the TV.